(3SYhO GdeWGdY dSYhO GdeWGdY ajeG JVefg GdEdZGR aj GSe MVQI hGdi eUQ ef GdYdhe GddhGeYs - (3YHO GdgGOj fLG Hf QVhGf fLG Hf eMeO GdCHjGQj GdeUQj,J (B1305 (3g` s
(3ChdgG (B:s
(3Gdaf GdCQHYhf ai GdJGQjN hcGf GdNJGe deG Cfg BNQ CMhGd GdCjGe hMcGjI CYeGd ZhGHQ GdCjGe s
(3BNQgG (B:s
(3hJe Ydi jO eDdag HeMQhSI eUQ YTGA djdI GdSHJ SGOS eYdheGJ YGe eKdi JGdi KGfi GdGSe hVYa Chdg , hPdc HYO eUMa GSeg hMGUd VQH Kef KGdKg ai cGedg hGdMeO ddg QH GdYGdejf , Bejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B262(3C (B- (3U(B316(3Cs
(3LeY ajg CQHYjf afkG ai TQM dZR HGSe ESeGYjd NOjhi eUQs
(3hGdehLhO efg Gdaf GdCQHYhf ai GdJGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B173 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B203s
Keywords: (3GdJGQjNs